The thermoregulatory effects of noradrenaline, serotonin and carbachol injected into the rat spinal subarachnoid space - Lopachin, Richard M. (1982)
1. We have examined the effects on thermoregulation in the rat of noradrenaline bitartrate (NA), 5-hydroxytryptamine hydrochloride (5-HT) and carbamylcholine chloride (CCh) injected into the lumbar spinal subarachnoid space via a chronic indwelling catheter. 2. Intrathecal injections of the monoamines and CCh reproducibly affected thermoregulation, whereas injections of control solutions had no effect. 3. Intrathecal injections of NA (0·01-0·30 μmol) produced a dose-dependent hypothermia associated with a decrease in tail skin vasomotor tone. Shivering activity was not depressed during the hypothermia and sometimes increased. Intrathecal administration of the α-adrenergic agonist clonidine (0·0175-0·070 μmol) elicited changes in T(c) and T(sk) similar to those induced by intrathecal NA. 4. Intrathecal 5-HT (0·030-0·90 μmol) elicited a dose-dependent hyperthermia accompanied by increased tail skin vasomotor tone and increased shivering. 5. CCh injected intrathecally (0·001-0·06 μmol) evoked a dose-dependent hyperthermia. During the period when core temperature was rising, tail skin vasomotor tone increased and shivering-like activity was present. Once the maximum core temperature had been reached, tail skin vasodilatation occurred. Vasodilatation persisted until core temperature had returned to normal. 6. Intravenous injections of 5-HT (0·30 and 0·90 μmol) or CCh (0·006 and 0·03 μmol) caused no thermoregulatory effect. The effects of these agents injected intrathecally were therefore not due to an action in the periphery. 7. Intravenous infusions of NA (0·06 and 0·10 μmol) produced hypothermia and transient tail skin vasodilatation. We suggest that an action at peripheral sites may have contributed to the effects produced by intrathecal injection of this monamine. 8. These findings suggest that spinal noradrenergic, serotonergic and cholinergic synapses may be importantly involved in the control of body temperature in the rat. The possible functional roles of these synapses and the putative spinal sites of action of the injected substances are discussed.